Active suspension control of two axle railway vehicle - Mohd. Amir Izat, Mhd. Rodzi (2009)
This project presents the dynamic modelling and control of railway vehicle active suspension systems. Active suspension in this project concerns on the lateral movement of the railway vehicle when a curved is meet. The vehicle type selected for this study is the two-axle vehicle. The active element is place on both leading and trailing wheelset to improve the curving performance. The wheelset curving performance and vehicle body acceleration evaluated will be compared for different curve radius, cant angle, and vehicle velocity input hence the actual parameters are used for railway vehicle simulation. The optimal controller was chosen to control the lateral and yaw deflections of the two axle railway vehicle. The active suspension wheelset with two axle vehicle show different kind of performances when the curve radius, cant angle and vehicle velocity input are change.